Gracillaria Associated Amphipod at Abalonesâ€™ Rearing Tank, Lombok Marine Aquaculture Development Center, Sekotong, Indonesia - Wibowo N. Jati1, Felicia Zahida Hery Setyabudi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2017)
Some benthic minute amphipods have been found at abalonesâ€™rearing tank, at Lombok Marine Aquaculture Development Center, Sekotong, West Nusa Tenggara, Indonesia. The minute amphipod community was found along with Gracillaria verrucosa which was harvested from Sekotong fishpond. There is some vigilance that it might be a pest that interferes the production of abalones. This research aims to reveal the type of the minute amphipod at the rearing tank. Morphological characters were examined to identify the Amphipod. Some slide was made to recognise and identify minute apparatus of the Amphipod. A hundred of Amphipod was reared in a small container to see their immediate behavior such as feeding or reproduction or other/s or its product. Some video were used to record for 30â€ to 60â€ to see the behavior of Amphipods. Result show that at least four types of Gammaridea present at the abalone culture pond. Some Amphipod was descent to abalone for some time, hop and perch to Gracillaria. Some Amphipods build a nest from pieces of Gracillaria in a tube form. There are two types of nest, firstly, small tube which were attached to the substrate and secondly, bigger tube which were float with the Gracillaria.